2016
DOI: 10.4081/gh.2016.407
|View full text |Cite
|
Sign up to set email alerts
|

To what extent does climate explain variations in reported malaria cases in early 20th century Uganda?

Abstract: Malaria case statistics were analysed for the period 1926 to 1960 to identify inter-annual variations in malaria cases for the Uganda Protectorate. The analysis shows the mid-to-late 1930s to be a period of increased reported cases. After World War II, malaria cases trend down to a relative minimum in the early 1950s, before increasing rapidly after 1953 to the end of the decade. Data for the Western Province confirm these national trends, which at the time were attributed to a wide range of causes, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…Similarly, in our analysis only a single malaria model was used, and recent work by Piontek et al (2014);Caminade et al (2014) and Wallace et al (2014) has highlighted the considerable uncertainty in individual impacts models. Tompkins et al (2016b) parameter ensembles for single location runs. Thus the limited ensemble size of initial conditions and modelling systems implies that the results of this study should be taken as merely indicative of potential impacts.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in our analysis only a single malaria model was used, and recent work by Piontek et al (2014);Caminade et al (2014) and Wallace et al (2014) has highlighted the considerable uncertainty in individual impacts models. Tompkins et al (2016b) parameter ensembles for single location runs. Thus the limited ensemble size of initial conditions and modelling systems implies that the results of this study should be taken as merely indicative of potential impacts.…”
Section: Discussionmentioning
confidence: 99%
“…These data provide 1900s malaria endemicity estimates for all Plasmodium parasites before human intervention occurred at a global scale. This dataset is a better estimate of the impact of environmental conditions on malaria burden, as limited malaria control measures were undertaken prior to the 1920s 55 . These data are binned into five categories: free, PR < 1%; hypoendemic, PR > 1% and PR < 10% ; mesoendemic, PR > 10% and < 50%; hyperendemic, PR > 50% and < 75%; and holoendemic transmission, PR > 75% 56 .…”
Section: Malaria Validation Datamentioning
confidence: 99%
“…The methodology examined the output Jacobians (the matrix of all first order function derivatives), a method that has also been employed for atmospheric models [ 42 44 ], but has the drawback of being dependent on the basic state employed. Parallel to the climate modeling approach, some studies employ ensembles of health models integrations with stochastic parameter perturbations [ 45 47 ]. These studies showed limited perturbations of a single model parameter could lead to a very large spread in the simulated transmission intensity in highland setting where temperature was close to the 18°C threshold.…”
Section: Introductionmentioning
confidence: 99%